2010
DOI: 10.1002/ejoc.201000597
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Tyrosine‐Derived Tetramic Acid Pigments from a Slime Mould

Abstract: A method for the total synthesis of naturally occurring 3-enoyltetramic acids derived from L-tyrosine is described, allowing for three chemical transformations to occur in one pot by using a multicomponent mixture. The sequence involves (1) a base-promoted Lacey-Dieckmann condensation, (2) a Michaelis-Becker reaction, and (3) a Wittig-Horner-Emmons reaction between the resulting 3-phosphonoacetyltetramic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…β‐Ketoamide 8′ was obtained as a crude product not amenable to further purification. An attempted cyclization of 8′ under conditions described in the literature for simple unprotected N ‐acyl tyrosinates failed to give 31 , a diastereomer of F‐14329 and chaunolidine A, but afforded the retro‐aldol product 30 instead (Scheme ).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…β‐Ketoamide 8′ was obtained as a crude product not amenable to further purification. An attempted cyclization of 8′ under conditions described in the literature for simple unprotected N ‐acyl tyrosinates failed to give 31 , a diastereomer of F‐14329 and chaunolidine A, but afforded the retro‐aldol product 30 instead (Scheme ).…”
Section: Figurementioning
confidence: 99%
“…b-Ketoamide 8' was obtained as ac rude product not amenable to further purification. An attempted cyclization of 8' under conditions described in the literature for simple unprotected N-acyl tyrosinates [15] failed to give 31,adiastereomer of F-14329 and chaunolidine A, but afforded the retro-aldol product 30 instead (Scheme 5). To favor Dieckmann cyclization over retro-aldol fragmentation, we introduced an N-2,4-dimethoxybenzyl (DMB) group, previously shown by Schlessinger et al to render b-ketoamide anions more nucleophilic.…”
mentioning
confidence: 99%
“…The phenol group of the tyrosine ethyl ester hydrochloride 9 was protected with TBDMSCl, resulting in 10 (81%). 34 A peptidic coupling between 10 and FA generated 11 (83%). The free alcohol of 11 was activated to a p -nitrophenyl carbonate 12 in the presence of pyridine (71%).…”
Section: Results and Discussionmentioning
confidence: 99%
“…To reach the biomimetic intermediate 6, retrosynthetic analysis revealed two Wittig-type olefinations (a) or (b). Indeed we and others have recently shown that activated acetyltetramic acids can be used in a variety of Horner-Wadsworth-Emmons 8 or Wittig 9 reactions to make long-chain-substituted tetramic acids from natural sources. Herein, we wish to describe our efforts to synthesize the polyunsaturated part of compound 6 from (R)-citronellal.…”
mentioning
confidence: 99%
“…Moreover, the one-pot diol cleavage-Wittig reaction sequences towards ester 18 and amide 19 from diol 13 have shown the feasibility of this strategy that we hope to apply to the synthesis of 6, through the a,b-unsaturated aldehyde 20, according to strategy (a). 8,9 In parallel, efforts are under way to synthesize an E,E,E biomimetic precursor analogous to 6, which may be useful for reactivity studies. Further details will be reported in due course.…”
mentioning
confidence: 99%